Evaluasi Aplikasi Pemesanan Tiket Menggunakan Metode System Usability Scale (SUS) dan Model D&M IS Success - Purba, Mariana; Dianing Asri, Sri; Noprisson, Handrie; Utami, Marissa; Iryani, Lemi; Marissa Utami (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
Software product development not only focuses on features but also usability aspects. User experience is very important in the evaluation of reusability to understand the user's interaction with the product or system. Reusability factors include user satisfaction, efficiency, and effectiveness to achieve specific goals. The main purpose of this study is to evaluate the usability aspect of online ticket booking applications. This evaluation process is important to identify development and improvements to user views and application usage satisfaction. In this study, the object studied was an online travel booking application in Indonesia. The research instrument uses a quantitative and qualitative mixed-method approach. For the quantitative approach, the System Usability Scale (SUS) is used and as a basis for a qualitative approach, the D&M IS Success Model approach is used. Based on the evaluation results, there are several points that should be improved including the interface design should be simple, the reduction in the size of memory used by applications, features to communicate with customer service easily, data integration, and time notifications to complete payments.